Emery-Dreifuss muscular dystrophy: linkage to markers in distal Xq28. Issue 2 (February 1993) - Yates, J R; Warner, J P; Smith, J A; Deymeer, F; Azulay, J P; Hausmanowa-Petrusewicz, I; Zaremba, J; Borkowska, J; Affara, N A; Ferguson-Smith, M A
Abstract : Emery-Dreifuss muscular dystrophy (EMD) is characterised by (1) early contractures of the Achilles tendons, elbows, and postcervical muscles, (2) slowly progressive muscle wasting and weakness with a predominantly humeroperoneal distribution in the early stages, and (3) cardiomyopathy with conduction defects and risk of sudden death. Inheritance is usually X linked recessive but can be autosomal dominant. Family linkage studies have mapped X linked EMD to the distal long arm of the X chromosome but precise genetic localisation has been hampered by the rarity of this condition. We report three new families with X linked Emery-Dreifuss muscular dystrophy studied with DNA markers from Xq27-qter and three previously published families typed for additional markers. No recombination was observed with the red/green cone pigment locus, RGCP (lod score, Z = 2.46), the factor VIII coagulant gene locus, F8C (Z = 6.39), or with DXS115 (Z = 4.94). Two recombinants were observed which mapped EMD distal to DXS15 (DX13) and DXS52 (St14) respectively. Multipoint linkage analysis gave odds exceeding 200:1 for EMD being distal to these markers. A multipoint analysis incorporating published data gave the map cen-DXS304-9cM-DXS15-3cM-DXS52-2 cM-(RGCP, EMD)-3cM-F8C-2cM-DXS115 with odds of 120:1 in favour of a location for EMD between DXS52 and F8C as compared to the next best position distal to F8C.